Klippel-Trenaunay-Weber syndrome with intracranial dural arteriovenous fistula and spinal arteriovenous shunt - Su, Xin; Ma, Yongjie; Zhang, Hongqi; Li, Guilin; Li, Jingwei (Human Brain, 2023)
Our clinical image revealed a case of Klippel-Trenaunay-Weber syndrome (KTWS) accompanied by a spinal arteriovenous shunt and an intracranial dural arteriovenous fistula. There have been few reports of KTWS patients developing dural arteriovenous fistulas. This clinical image highlights the strong association between KTWS and CNS vascular malformations. It is important to note that KTWS patients are at risk of developing central nervous system vascular diseases. Therefore, early detection and screening are recommended.